1983
DOI: 10.4141/cjss83-008
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Electrical Conductivity With Total Dissolved Salts and Cation Concentration of Sulfate-Dominant Soil Extracts

Abstract: CHeNc, C., Sovvprr.slor, T. G., CanEroor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 3 publications
1
28
0
Order By: Relevance
“…The experimental site and manure used in this study were described previously (Sommerfeldt and Chang 1985 In the recovery analysis, EC data were converted ro estimated soluble salts (Chang et al 1983). …”
Section: Methodsmentioning
confidence: 99%
“…The experimental site and manure used in this study were described previously (Sommerfeldt and Chang 1985 In the recovery analysis, EC data were converted ro estimated soluble salts (Chang et al 1983). …”
Section: Methodsmentioning
confidence: 99%
“…Richards (1974) established a lineal relationship between EC and total dissolved salts (TDS), while other authors have demonstrated that a lineal correlation does not always exist between the EC and the corresponding ionic species Chang et al, 1983;Darab et al, 1980;Rhoades et al, 1989;Simo´n et al, 1994). The formation of ionic pairs, mainly Ca 2 þ , Mg 2 and SO 4 2 À ions (Alzubaidi & Webster, 1983;Timpson & Richardson, 1986), in highly saline solutions is the main cause of this anomaly, because ion mobility in the extract is decreased (Csillag et al, 1995;Darab et al, 1980;Marion & Babcock, 1976;Sposito, 1984).…”
mentioning
confidence: 94%
“…Many authors have studied the possible relationship between ECe and the salt concentration of a soil, in an attempt to assess the validity of this parameter as an indicator of soil salinity. Richards (1974) established a linear relationship between EC and total dissolved salts, while other authors have demonstrated that a linear correlation does not always exist between the EC and the corresponding ionic species (Alvarez et al 1997;Chang et al 1983;Darab et al 1980;Rhoades et al 1989;Simon et al 1994). The formation of ionic pairs, mainly Ca 2+ , Mg 2+ , and SO 2− 4 ions (Timpson and Richardson 1986), in highly saline solutions is the main cause of this anomaly, because ion mobility in the extract is decreased (Darab et al 1980; Csillag et al 1995;Marion and Babcock 1976;Sposito 1984).…”
Section: Ionic Composition and Relation To Ecementioning
confidence: 91%